PENGEMBANGAN E-MODULE KALKULUS I SEBAGAI PANDUAN MAHASISWA UNTUK MENGOPTIMALKAN INDIVIDUAL LEARNING - Sunismi Sunismi; Abdul Halim Fathani (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2015)
The purpose of this study is to arrange the e-module of Calculus I as a student guidance in optimizing individual learning. The method used here is a development research method. The model applied in this research is Four-D which includes stages of define, design, develop, and disseminate. The development results according to Four-D model are as follows: in the Define stage, it is known that the results of the analysis to the needs of student and lecturer shows that most of the students have difficulties in learning Calculus I because the lecturer uses a text book. In the text book, the concept is presented abstractly that makes the students difficult to understand. Hence, it is necessary to develop teaching materials which are easier to understand by the students, one of them is e-module. In the Design stage, the initial draft of e-module of Calculus I is designed which includes introduction (there are preface, instructions in using e-module, material descriptions, prerequisites, and learning objectives), the material and examples, exercises, summary, competency tests (in interactive way), the solutions, feedbacks, and a list of references. The Develop stage is where the prototype of e-module is created and it means the e-module is established. Then, initial trials related to the content of e-module are performed through the assistances from the expert and the lecturer of Calculus I. The appraisements of both the expert and the lecturer explain that the e-module is valid, so that the content of the e-module of Calculus I in this study is proper to be established.